Large Display Research Overview - Czerwinski, Mary; Robertson, George; Meyers, Brian; Smith, Greg; Robbins, Daniel; Tan, Desney (Extended Abstracts at CHI 2006 Conference on Human Factors in Computing Systems, 2006)
As large displays become more affordable, researchers are investigating their effects on productivity, and techniques for making the large display user experience more effective. Recent work has demonstrated significant productivity benefits, but has also identified numerous usability issues with current software design not scaling well. Studies show that larger displays enable users to create and manage many more windows, as well as to engage in more complex multitasking behavior. In this overview, various usability issues, including problems around accessing windows and icons at a distance, window management, and task management, will be discussedSeveral novel interaction techniques that address these issues and make users more productive across multiple sizes of displays will be explored.